Ethno-National Policy of Ukraine in the Context of National Security: Problems and Prospects - Kravets, Anastasia; Vyshnevska, Iryna (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2024)
The process of national consolidation is closely related to the implementation of a consistent ethno-national policy in accordance with modern conditions. The integration of Ukraine into the European Union is impossible without the regulation of ethno-national development processes in accordance with the standards of the European Union. The effectiveness of the state’s ethno-national policy depends on the extent to which its principles and tasks reflect the ethno-national situation in the country, ensure the participation of civil society in the processes of regulating ethno-national relations. The legislation of Ukraine in the field of ethno-national policy was formed under the influence of internal international relations and international legislation. The analysis of the content of the national legislation shows that it enshrines fundamental international norms regarding the protection of national minorities, at the same time, it also has certain shortcomings: blurred provisions, lack of specification of basic terms, obsolescence of the legislative acts themselves, etc. New political realities require revision of most of the adopted legislative acts. Neglecting issues of ethno-national development carries the danger of turning the ethno-national factor from a cultural asset into a source of conflicts and contradictions, leading to the loss of the тational security and country’s territorial integrity. Unregulated relations between ethno-cultural groups aggravate the problems of inter-ethnic communication, create conflict situations, etc. The adoption of the Concept of the State target national and cultural program “Unity in Diversity” for the period until 2034, which was developed in close consultation with national minorities (communities) with the involvement of representatives of the European Commission, the Council of Europe, and embassies of ethnically related national minorities (communities) of Ukraine. Proces konsolidacji narodowej jest ściśle związany z realizacją spójnej polityki etniczno-narodowej dostosowanej do współczesnych warunków. Integracja Ukrainy z Unią Europejską jest niemożliwa bez uregulowania procesów rozwoju etniczno-narodowego zgodnie ze standardami Unii Europejskiej. Skuteczność polityki etniczno-narodowej państwa zależy od tego, w jakim stopniu jej zasady i zadania odzwierciedlają sytuację etniczno-narodową w kraju, zapewniają udział społeczeństwa obywatelskiego w procesach regulacji stosunków etniczno-narodowych. Ustawodawstwo Ukrainy w dziedzinie polityki etniczno-narodowej zostało ukształtowane pod wpływem wewnętrznych stosunków międzynarodowych i ustawodawstwa międzynarodowego. Analiza treści ustawodawstwa krajowego pokazuje, że zawiera ono podstawowe normy międzynarodowe dotyczące ochrony mniejszości narodowych, a jednocześnie ma pewne niedociągnięcia: nieprecyzyjne przepisy, brak zdefiniowania podstawowych terminów, przestarzałość aktów prawnych itp. Nowe realia polityczne wymagają rewizji większości przyjętych aktów prawnych. Zaniedbanie kwestii rozwoju etniczno-narodowego niesie ze sobą niebezpieczeństwo przekształcenia czynnika etniczno-narodowego z dobra kulturowego w źródło konfliktów i sprzeczności, prowadząc do utraty bezpieczeństwa narodowego i integralności terytorialnej kraju. Nieuregulowane stosunki między grupami etniczno-kulturowymi pogłębiają problemy komunikacji międzyetnicznej, tworzą sytuacje konfliktowe itp. Ważnym krokiem jest przyjęcie koncepcji państwowego docelowego programu narodowego i kulturalnego „Jedność w różnorodności” na okres do 2034 roku, który został opracowany w ścisłej konsultacji z mniejszościami narodowymi (społecznościami) przy udziale przedstawicieli Komisji Europejskiej, Rady Europy i ambasad etnicznie powiązanych mniejszości narodowych (społeczności) Ukrainy.
Polityka etniczno-narodowa Ukrainy w kontekście bezpieczeństwa narodowego: problemy i perspektywy
Keywords: ethno-national policy; national security; national minority; ethno-national processes; polityka etniczno-narodowa; bezpieczeństwo narodowe; mniejszość narodowa; procesy etniczno-narodowe